Identification of rice cropping areas in the Mekong Delta using radar imagery - Balababa, Laarni L.; Schumann, Robert L.G.; Adrianasolo, Haja; Tinsley, Richard; Government of United Kingdom (Bangkok : Asian Institute of Technology, 1997)
Seven multi-temporal ERS SAR PRI images acquired over the period May to December 1996 were used to delineate and map areas under different rice cropping systems in the Mekong Delta, Vietnam. Five change index maps were generated from the six images acquired and a 3 dB threshold was used to classify each pixel as having an increasing, decreasing or constant backscattering. These change index maps were used to create a composite image having 202 classes where the backscatter values were subjected to Hierarchical clustering analysis. Different clusters were formed and evaluated until homogeneous clusters were generated. A cluster was classified as single cropped, double cropped or non-rice based on its resemblance to the known backscatter profiles of the two cropping systems. Otherwise, it was classified as non-rice. The different cropping patterns under the double cropping systems were identified at each district and then generalized into the provincial level. In Can Tho province, Dong Xuan - He Thu cropping pattern is the most prevalent practice since most fields in this area are irrigated. He Thu - Mua pattern is the most widely adopted in Soc Trang which is mostly rainfed rice. On the other hand, Minh Hai province is divided into rice and non-rice areas. Almost 48% of the total area is utilized into shrimp farming, mangrove plantations and other non-rice crops while the rest are dedicated to single and double rice cropping. The single cropped areas are located near the coastal areas where there is permanently saline soils while the double cropped areas are located in the more inland areas where the level of salinity is lower. He Thu - Mua is still the popular cropping practice in the double cropped area. These information about cropping patterns would provide ideas about the resources possess by each province regarding rice cultivation as well as the limitations and constraints they are facing to intensify cropping. Validation of the classification was done based on the previous researches about the study area and areas of conflicts were noted. The discrepancy between the result and the previous studies was resolved by the information about the completed agricultural structures in the area in 1995 and 1996 that made possible the intensification of cropping in the problematic areas.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Geographic information systems; Agriculture -- Vietnam -- Mekong Delta